The Association of Caries Increment Dynamics in Preschool Children with Risk Factors: The 3-Year Prospective Study - Pilbauerova, Nela; Cermakova, Eva; Koberova Ivancakova, Romana; Suchanek, Jakub (International journal of environmental research and public health, 2020)
This prospective study monitored the dental status, the presence of plaque, and cariogenic microorganism levels of identical children over three years. The aim was to determine the dynamics of caries increment as well as the relationship between risk factors and caries prevalence. A total number of 125 children (72 boys and 53 girls) was included in the study, with an average age of 3.95 ± 0.06 years at the baseline. During the clinical examination at the nursery schools, the presence of dental plaque was recorded, and saliva samples were collected from the tongue of children for the DentoCult SM test providing easy detection of mutans streptococci from saliva samples. At baseline, 65.6% of the children had no caries, 4% had restored teeth with fillings or crowns or missing teeth due to caries, and 30.4% had at least one untreated caries. The percentages of intact teeth, restored or missing teeth, and untreated caries were 52.8%, 8.8%, 38.4% in the second year and 49.1%, 13.8%, and 31.1% in the third year. The dmft index value was 1.41 ± 0.24 in the first year, 2.29 ± 0.30 in the second year, and 2.33 ± 0.31 in the third year. There was a significant correlation between plaque presence and dt and dmft values (p < 0.05; the statistical analyses were performed using the Kolmogorov-Smirnov test). This 3-year longitudinal study highlighted the importance of examining both the oral hygiene and the level of cariogenic microorganisms when undertaking the evaluation of caries risk evaluation in preschool children.
Keywords: zubní kaz; zubní plak; Female; DMF Index; předškolní dítě; ženské pohlaví; sliny; longitudinální studie; caries increment; lidé; prospective study; Dental Caries; preschool children; Risk Factors; trvalá zubní náhrada; prospektivní studie; Saliva; Male; Prospective Studies; orální hygiena; Dental Restoration, Permanent; Child, Preschool; rizikové faktory; Dental Plaque; longitudinal study; mužské pohlaví; Oral Hygiene; Longitudinal Studies; Humans